Contributions/Roles of Millennial and Gen Z in Utilising Digital Technology - Riecha Priyadi Fhany Damanik; Derselli P. Silitonga (Jurnal Sosiologi Nusantara, 2025)
The millennial generation and generation Z play a strategic role in the era of modernization influenced by technological advances and globalization. Generation actively contributes to economic, cultural, and social aspects with the characteristics of being adaptive, digital-savvy, critical and innovative, open, free, critical, and brave by fostering opportunities and chances to innovate. Through qualitative methods based on secondary data analysis, this study reveals how this generation accelerates current social change. Despite facing economic challenges and financial pressures, this generation is still able to contribute to a more advanced and inclusive society. Their technological skills and entrepreneurial spirit create opportunities for innovation, especially in the digital economy and social movements that support inclusivity and diversity. Driven by technological advances, the influence of globalization, these two generations have extraordinary abilities to adapt, think critically, and create innovations that can affect many aspects of life, such as the economic, cultural and social fields.